PEMIDANAAN TERHADAP RESIDIVIS PENGGELAPAN MOBIL RENTAL - Karina, Ica; Sinaga, Mancur (JURNAL JUSTIQA, 2023)
This study aims to determine the punishment for recidivists of rental car embezzlement and to find out the obstacles that arise in the punishment of recidivists of rental car embezzlement.The data used is through literature study by reading, quoting, studying, studying existing literature or materials as well as laws and regulations related to the problem being studied. The material collected in this research was analyzed qualitatively and juridically.The results of this study indicate that the background of the panel of judges imposing a light sentence for a recidivist is due to facts revealed in court, facts arising from valid evidence in court and evidence from witness statements. The judge in deciding a case is required to give a fair decision, because basically the judge's decision in a criminal case will have a big impact on both the perpetrator and the victim. The judge in trying a criminal case must try to find and prove material truth based on the facts in the trial. The recidivism factor is considered as a weighting reason for the crime of the perpetrator being proven guilty of having committed a crime and the perpetrator committing another crime. The sentence imposed by one judge and the perpetrators of other criminal acts is different even though the criminal acts are the same, this is due to the consideration of the judge before imposing a sentence on the perpetrator.